BDE-209 and DBDPE induce male reproductive toxicity through telomere-related cell senescence and apoptosis in SD rat. (January 2021) - Li, Xiangyang; Liu, Jianhui; Zhou, Guiqing; Sang, Yujian; Zhang, Yue; Jing, Li; Shi, Zhixiong; Zhou, Xianqing; Sun, Zhiwei
Graphical abstract: Highlights: BDE-209 and DBDPE led to the decline of sperm quality and quantity in SD rat. BDE-209 and DBDPE exposure reduced telomere length and telomerase activity. BDE-209 and DBDPE caused telomere-related cell senescence and apoptosis in testis. BDE-209 induced more severe impacts on male reproduction compared with DBDPE. Abstract: Decabrominated diphenyl ether (BDE-209) and decabromodiphenyl ethane (DBDPE) are common flame retardants utilized in many kinds of electronic and textile products. Due to their persistence and bioaccumulation, BDE-209 and DBDPE extensively exist in the surrounding environment and wild animals. Previous studies have indicated that BDE-209 could induce male reproductive toxicity, whereas those of DBDPE remains relatively rare. In this study, we investigated the effects of both BDE-209 and DBDPE on reproductive system in male SD rats, and explored the potential mechanisms under the reproductive toxicity of BDE-209 and DBDPE. Male rats were orally administered with BDE-209 and DBDPE (0, 5, 50 and 500 mg/kg/day) for a 28-day exposure experiment. The current results showed that BDE-209 and DBDPE led to testicular damage in physiological structure, decreased the sperm number and motility, and increased the sperm malformation rates in rat. Moreover, BDE-209 and DBDPE could damage the telomeric function by shortening telomere length and reducing telomerase activity, which consequently caused cell senescence and apoptosis in testis of rat. This could contribute to the decline of sperm quality and quantity. In conclusion, BDE-209 and DBDPE led to reproductive toxicity by inducing telomere dysfunction and the related cell senescence and apoptosis in testis of SD rat. Comparatively, BDE-209 had more severe effects on male reproduction. Our findings may provide new insight into the potential deleterious effects of BFRs on male reproductive health.